Study of Medicinal Plants Ethnopharmacy in Antihypertension in Karang Tunggal, Tenggarong Seberang, East Kalimantan - Pratiwi, Putri Rinda; Juliyanti, Juliyanti; Biondi, M Ecky; Supardi, Supardi (Sebatik, 2024)
Ethnopharmacy is a branch of pharmaceutical science that studies the use of medicines and treatments practiced by specific ethnic regions or groups. Its scope primarily includes medicines and treatments derived from natural ingredients. Hypertension is a condition characterized by elevated blood pressure, with systolic blood pressure equal to or greater than 140 mmHg and diastolic blood pressure equal to or greater than 90 mmHg. This study aims to identify and document medicinal plants used as antihypertensive remedies in Karang Tunggal Village. The research employed descriptive and quantitative methods, with sampling conducted using the purposive sampling technique. Data were collected by identifying medicinal plants based on their local names, the plant parts used, and their Use Value (UV). The UV indicates the species that are considered the most significant within the community. The findings revealed 14 medicinal plants with antihypertensive properties, including cucumber, Mengkudu (noni), Sungkai leaves, Salam leaves, among others. Among these, cucumber demonstrated the highest Use Value (UV) at 0.15. The study also documented the methods of usage, which included drinking and eating, while the dosage forms involved decoctions, juices, and raw pieces. The processing methods primarily consisted of boiling, squeezing, and using the plants whole.